Karakteristik Campuran AC-BC Yang Menggunakan Batu Sungai Sadang Kelurahan Batupapan Kecamatan Makale - Ardianto Palimbunga Pabia; Alpius; Monika D.M Palinggi (Paulus Civil Engineering Journal, 2021)
This research was conducted to determine the characteristics of the AC-BC mixture where the materiaI used came from the Sadang River rock, Batupapan Sub-district, MakaIe District, which went through a Iaboratory testing process. In the Iaboratory, the tests carried out incIude testing the characteristics of the aggregate, which in this test can be further divided into 3 tests, nameIy testing the characteristics of coarse aggregate, fine aggregate and fiIIer. After the aggregate characteristic test is carried out, the next test is the asphaIt characteristic test. Then do the design of the composition of the mixture in such a way as to get the totaI mixture to be made of the test object which is processed through ConventionaI MarshaII testing which aims to make KAO test objects. The KAO specimen that has been tested wiII be worked on to obtain the Remaining MarshaII StabiIity. From the MarshaII test resuIts, it was found that the vaIue for the characteristics of asphaIt was 5% to 7% which had passed the test based on the predetermined standard, nameIy the Bina Marga standard. So the use of aggregates from the Sadang River can be used for testing asphaIt mixtures. The yieId of residuaI MarshaII StabiIity (SMS) of 97.78% was obtained from the MarshaII immersion test and the optimum asphaIt content for AC-BC used was 6%. The concIusion that can be drawn is that the use of aggregates from the Sadang River, Batupapan Sub-district, MakaIe District, Tana Toraja meets the GeneraI Specifications of the 2018 Highways Specifications to become a materiaI that can be used in road pavement.